A Three-Stage Game Analysis of Private Lending Rate Ceiling: Necessity, Impact, and Solution. (23rd August 2022) - Tao, Ran; Chai, Jiayue
Abstract : The ceiling on private lending interest rates is a powerful financial tool to maintain financial stability and reduce usury. Especially now that peer-to-peer lending has encountered some challenges, the ceiling is an essential way to regulate this market. The purpose of this paper is to analyze the necessity and the impact of such a powerful tool and also to find the optimal solution to determine it. The paper proves the ceiling on private lending interest rates is an inevitable choice by using an evolutionary game. However, it is shown that the lowering of the ceiling on private lending interest rates will increase both the difficulty of financing for SMEs and the default rate. Two optimal solutions to the ceiling are obtained in this study, which also prevent an increase in borrowing costs.